Social-psychological aspects of motivation to recycle behaviour among household residents - Jasmine Adela Mutang; Rosnah Ismail; Chua, Bee Seok; Ferlis Bahari; Lailawati Madlan Endalan; Chan, Alfred Huan Zhi; Walton Wider; Rickless Das (Universiti Malaysia Sabah, 2015)
Waste projection is increasing and most landfills in Malaysia are running out of space. Due to that, waste management is now becoming a major challenge. The most sustainable solution is by doing some sustainable practices such as recycling. Since 1993 the government has launched several recycling campaigns and implemented the National Recycling Policy. However, only 10.5% of solid waste was recycled up to now which is far below than of in developed countries. Nevertheless the government is optimistic that that the target of 22% recycling by 2020 will be achieved if there is a positive flow pattern in sustainable practices in particular recycling behaviour among Malaysian. Understanding public attitude and behaviour towards recycling domestic waste are some useful keys to improve current waste management. Thus this study attempts to identify their attitude towards recycling and reasons they carried out (or reluctant) any recycling activities. A total of 486 households in Kata Kinabalu were involved in this study. An open-ended format was selected to allow respondents express their answers freely to capture their recycling attitude. Preliminary coding, categorization, axial coding and cross-tabulations were run accordingly based on indigenous psychological approach. Findings led to the discovery of their recycling attitudes which are (i) attitudes towards the environment; (ii) attitudes towards waste management and & cleanliness; (iii) attitudes towards sustainable lifestyle and community wellbeing; (iv) negative attitudes; and (v) benefits to others and third parties. The findings will be discussed further.